The transformative power of Europe reconsidered: Euroscepticism, Europhilia and democratisation in Europe’s periphery - Toth, Fanni (2018)
Since the end of the Cold War, the political development and democratisation of the post-communist countries to the east of the EU has drawn considerable attention from academic scholars. Initially, this was characterised by optimism, with scholars praising the EU for exporting institutional democracy through its mechanism of conditionality. This research, however, has given little attention to the micro-level foundations of the process. Yet the recent increase in Euroscepticism and anti-democratic, extremist tendencies have pointed to the importance of individual attitudes, even leading academics to argue that a democratic backsliding is taking place in Central and Eastern Europe. This thesis intends to re-examine the case of the EU’s transformative power, focusing specifically on its micro-level impact on the political attitudes of citizens and elites. The research question thus asks: to what extent does the EU have a transformative power on political attitudes? The thesis consists of three research papers that use quantitative and qualitative methods to examine EU influence on two types of actors, the general population and bureaucratic elites, focusing on two types of attitudes: support for democracy and support for the EU. The overall findings show that the Union does have a micro-level impact on attitudes both at the elite and citizen levels, though this is contingent on the nature of the relationship with the EU, as well as individuals’ support for the Union. In the first paper, the thesis demonstrates that the EU can affect attitudes towards democracy among the post-communist population, although this is contingent on the state’s association with the Union: when this is simply economic or political, the effect is positive; however, when the association involves integration as a candidate or member state, a rise in Euroscepticism among the population can in fact lead to lower levels of democratic support. This finding shows that Euroscepticism has an important role in altering the EU’s transformative influence on individuals in states integrated within the EU. Indeed, the consequences of this could be highly significant, especially when it comes to political and bureaucratic elites whose daily job affects the politics and policy of their countries. As a result, the second paper examines the EU’s effect on the attitudes of civil servants working in the national bureaucracies of the new member states. Using international socialisation theory, the paper shows that civil servants generally tend to support the EU, and this is higher among officials whose daily work brings them into contact with it. In addition, the analysis further explores the scope conditions that facilitate socialisation, revealing that both the quantity and quality of contact with EU-related issues – in terms of prolonged exposure as well as interpersonal contact – matter in explaining the sources of variation in levels of support. Lastly, to examine more closely how bureaucrats see the EU, the third paper uses a more in-depth qualitative study to explore the perceptions of Brussels-based diplomats on the economic, political and security dimensions of the Union. Through a comparative analysis, the paper once again shows that the state-level relationship with the EU can affect the perspectives formed by elites. Using original interview data, the research develops a typology of four types of “perspectives of the EU”, based on two dimensions: expectations from the EU and evaluation of the EU. The paper’s main argument is that the state-level relationship between the Union and the home country can greatly affect how elites representing those states perceive the Union. The main contributions of the thesis relate to a deeper understanding of the EU’s individual-level transformative power, through a discussion of its objects (citizens and elites), its mechanisms (direct and indirect), its scope (internal and external) and its outcomes (attitudes towards democracy and the EU). First, it demonstrates that the EU has a real and measurable effect in changing the perceptions of both citizens and elites in post-communist states. Second, it highlights that its impact works both through indirect mechanisms of a state-level political association, as well as direct mechanisms of international socialisation. In addition, it also reveals that Euroscepticism can act as a moderator, turning the EU’s positive democratising effect into a negative one, thus bringing together the literature on the transformative power of Europe with research on attitudes towards the EU and Euroscepticism. Third, it demonstrates that the EU has a transformative power both internally and externally, including non-accession third states. Lastly, it shows that the EU’s transformative power can influence attitudes towards democracy and the EU. Ultimately, the overall findings show that the Union has an impact on the attitudes of both elites and citizens, though this is contingent on the nature of the relationship with the EU, as well as individuals’ support for the Union.